International Freight Transportation Problems Under GMS-CBTA: Case Study of Thailand-Cambodia - Pratan Uttamapurna; Jaruwit Prabnasak; Ronnachai Tiyarattanachai (My University, 2019)
Abstract The governments of Thailand and Cambodia have enacted a policy under the GMS agreement to facilitate and increase trade and transport capacity. One of the key components is to improve land transport performance on the designated routes between Bangkok and Phnom Penh under the GMS-CBTA. However, the policy has not been considered effective as expected because licensed logistic companies still do not use that privilege. They also use the traditional method in which cargo is transhipped by local trucks at the borderline. In light of the problem, this study systematically investigated the root causes of the agreement ineffectiveness. Some recommendations for improving the performance of operation are given.
Keywords: Global trade and economics